Plan de negocio para la comercializadora de productos Gove Nails (2023)
A market investigation was carried out with the objective of building a business plan supported by the Sensory Marketing model in order to improve sales productivity and profitability of the importer and marketer Gove Nails, Medellín, Colombia. The methodology used is part of the management approach of organizations, which aims to ensure that an organization operates efficiently in achieving its goals through optimal planning of material and human resources, using observation as a data collection technique.